Fuzzy Measures of Monetary and Non-monetary Deprivations in Tunisia - Ben Hassine, Oula; Bouras, Hela (International Journal of Economics and Financial Issues, 2022)
The objective of this paper is to provide a measure of deprivation in Tunisia. The focus will be on non-monetary deprivation which will complement the profile of the poor in the country. The work is carried out on Tunisian data from the national survey on the budget, consumption, and the household’s standard of living (2015). The study tries to explore, in addition to the monetary dimension, the deprivations in Tunisia in the essential dimensions of a dignified and respectable human life: housing, education and health. The results obtained show a great disparity in monetary and non-monetary deprivation, particularly in the housing and education dimensions. Household characteristics seem to be an important element in the extent of deprivation. These include the location, region of residence as well as the socio-economic characteristics of the household head. The present paper stands out from several recent works on the phenomenon in Tunisia, based mainly on monetary indicators. By this aspect, this study contributes to a better understanding of poverty in the country.